Models of ecological renovation of industrial buildings for the creation of shopping, entertainment or recreational complexes - Zdor Nikita S. (Архитектон)
The article examines the key features of the functional planning and spatial architectural treatment of the typological group of public buildings and structures during renovation of industrial buildings in coastal areas in order to create promising models of two different types of multifunctional spaces: a shopping and entertainment complex, and a public park. Both approaches exploit the structural and spatial advantages of these buildings and modern architectural-ecological techniques, such as: adaptive reuse, structural reinforcement, and integration of natural light and environmentally friendly materials. The key differences lie in their focus: shopping and entertainment centers emphasize commercial activities and leisure through a dynamic shopping environment, while public parks give preference to green areas and outdoor recreation, integrating extensive landscape design and environmental sustainability methods into the project. Overall, these renovation models not only improve the urban environment, but also contribute to the well-being of the population and restoration of the environment in the area.